The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.22175/mmb2018.07.0018
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Muscle Fiber Characteristics Based on Muscle Fiber Volume in Porcine Longissimus Muscle in Relation to Pork Quality

Abstract: In livestock science and meat science, muscle fiber characteristics have been evaluated based on a cross-sectional area (CSA) of muscle fiber. However, muscle fiber is not planar but cylindrical. Thus, muscle fiber volume and volume-based characteristics were evaluated in this study. In addition, their relationships to pork loin quality was assessed and compared with that of CSA-based muscle fiber characteristics. Muscle fiber type IIB was underestimated by CSA-based evaluations with 1.6 times in fiber size an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 23 publications
2
18
0
Order By: Relevance
“…2A); however, muscle fiber composition (relative area) did not differ between the F-Vertical and M-Vertical. The size and composition relationships in glycolytic fibers (IIX and IIB) with pH and tenderness observed in the present study are in accordance with the findings in previous studies that demonstrated their positive or negative correlations with pH or tenderness, respectively, regardless of the animal species, breed, gender, age, and muscle type (Choi and Kim, 2009;Joo et al, 2013;Karlsson et al, 1993;Kim et al, 2013a;Kim et al, 2018;Larzul et al, 1997;Ryu et al, 2008). The CIE L* and CIE a* in meat color are highly affected by the fiber size and composition (Hwang et al, 2010;Kim et al, 2010;Kim et al, 2013a;Ozawa et al, 2000), that is, oxidative fibers are positively correlated with CIE a*, whereas glycolytic fibers are negatively correlated with CIE a* but positively correlated with CIE L* due to their diverse reliance on oxygen and consequent demands of myoglobin for energy metabolism of different muscle fiber types (Cassens and Cooper, 1971;Kim et al, 2010;Ozawa et al, 2000;Whipple et al, 1992).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…2A); however, muscle fiber composition (relative area) did not differ between the F-Vertical and M-Vertical. The size and composition relationships in glycolytic fibers (IIX and IIB) with pH and tenderness observed in the present study are in accordance with the findings in previous studies that demonstrated their positive or negative correlations with pH or tenderness, respectively, regardless of the animal species, breed, gender, age, and muscle type (Choi and Kim, 2009;Joo et al, 2013;Karlsson et al, 1993;Kim et al, 2013a;Kim et al, 2018;Larzul et al, 1997;Ryu et al, 2008). The CIE L* and CIE a* in meat color are highly affected by the fiber size and composition (Hwang et al, 2010;Kim et al, 2010;Kim et al, 2013a;Ozawa et al, 2000), that is, oxidative fibers are positively correlated with CIE a*, whereas glycolytic fibers are negatively correlated with CIE a* but positively correlated with CIE L* due to their diverse reliance on oxygen and consequent demands of myoglobin for energy metabolism of different muscle fiber types (Cassens and Cooper, 1971;Kim et al, 2010;Ozawa et al, 2000;Whipple et al, 1992).…”
Section: Discussionsupporting
confidence: 93%
“…Muscle fibers were leaned at 51.33° to 69.00° in the porcine LTL muscle, which is within the range of previous observations in porcine LTL (48.00° to 83.33°) or bovine longissimus lumborum (31.36° to 53.90°) muscles (Kim et al, 2018;Derington et al, 2011).…”
Section: Discussionsupporting
confidence: 87%
“…The muscle histological sample collection site on the carcass, tissue orientation during mounting and freezing, and avoidance of measurements of myofibers that were sectioned at oblique angles (see Myofiber characteristics subsection of Materials and Methods) were undertaken to minimize error in determinations of myofiber types, size, and numbers. However, it is recognized that the number of myofibers apparent in a muscle cross section will differ from the number of myofibers in the entire anatomical muscle due to intrafascicular termination of myofibers, and that the size of myofibers, in particular of fast glycolytic (type 2X or 2B) myofibers, may be underestimated using histological techniques compared with newer volumetric methods (Kim et al, 2018). However, the methods used in the present study provide meaningful comparisons between the muscling lines, as in our previously published studies using these techniques (Greenwood et al, 2006a(Greenwood et al, , 2006b(Greenwood et al, , 2009.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Muscle fiber (long, narrow, multinucleated cells) characteristics such as fiber size, fiber type dissemination, and relative composition have a linkage to meat quality attributes including color, tenderness, water holding capacity (WHC) and sensory qualities [28]. Connective tissue principally made of fibers of collagen which are straight, inextensible and non-branching and of elastin which is elastic, branching and yellow becomes much more resilient to breakdown by under a three-dimensional network formation and a high tensile strength development during animal's tissue maturation influences the quality attributes of meat to consumers as meat tenderness or texture is regarded in high esteem [26,29].…”
Section: Meat Muscle Structure and Effect On Meat Quality As Foodmentioning
confidence: 99%